2022
DOI: 10.1002/cam4.5501
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative systemic immune‐inflammation index as a significant prognostic factor after TURBT in patients with non‐muscle‐invasive bladder cancer: A retrospective study based on propensity score matching analysis

Abstract: Objective To investigate the association of the preoperative systemic immune‐inflammation index (SII) with recurrence‐free survival (RFS) after transurethral resection of the bladder tumor (TURBT) of non‐muscle‐invasive bladder cancer (NMIBC) using propensity score matching (PSM) analysis. Methods The clinicopathological characteristics and follow‐up data of NMIBC patients were collected retrospectively from two tertiary medical centers. A 1:1 PSM analysis was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…11 studies (involving 12 datasets) comprising 10577 patients reported on the prognostic effect of preoperative SII on RFS in UC patients ( 11 , 13 , 18 , 19 , 23 , 24 , 26 , 27 , 29 , 30 , 32 ). The pooled analysis demonstrated that higher preoperative SII in UC patients was an independent predictor of RFS (HR = 1.240, 95% CI 1.097-1.403, p=0.001), with significant heterogeneity (I 2 = 78.0%, p<0.001) ( Figure 4 , Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 studies (involving 12 datasets) comprising 10577 patients reported on the prognostic effect of preoperative SII on RFS in UC patients ( 11 , 13 , 18 , 19 , 23 , 24 , 26 , 27 , 29 , 30 , 32 ). The pooled analysis demonstrated that higher preoperative SII in UC patients was an independent predictor of RFS (HR = 1.240, 95% CI 1.097-1.403, p=0.001), with significant heterogeneity (I 2 = 78.0%, p<0.001) ( Figure 4 , Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…After having read the titles and abstracts, 35 potentially eligible papers underwent full-text reviewing. Finally, 19 studies that comprised 12505 patients were included in this meta-analysis (11,(13)(14)(15)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). All the included studies have been published within the last 5 years (2019-2023); 13 studies focused on BC, 5 studies about UTUC, and the last one was on mixed (BC and 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Finally, 19 studies that comprised 12505 patients were included in this meta-analysis [10,[12][13][14][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. All the included studies have been published within the last 5 years (2019-2023); 13 studies focused on BC, 5 studies about UTUC, and the last one on mixed(BC and UTUC).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Prognostic signi cance of SII on RFS in patients With UC 11 studies (involving 12 datasets) comprising 10577 patients reported on the prognostic effect of preoperative SII on RFS in UC patients [10,12,17,18,22,23,25,26,28,29,31]. The pooled analysis demonstrated that higher preoperative SII in UC patients was an independent predictor of RFS (HR = 1.240, 95% CI 1.097-1.403, p = 0.001), with signi cant heterogeneity (I 2 = 78.0%, p < 0.001) (Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…As in many previous studies, the SII is an important tool for predicting the prognosis and survival rate of patients with malignant tumors, spontaneous cerebral hemorrhage, and cerebral infarction. This index could provide an accurate assessment of a patient's inflammatory and immune status, allowing clinicians to gain a better understanding of the patient's condition and develop an appropriate treatment plan [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%